Experimental Investigation and CFD Modelling of Storage Tank Breathing - Natalie Schmidt; Michel Sundermann; Jens Denecke; Jürgen Schmidt; Michael Davies (Chemical Engineering Transactions, 2022)
Experiments were performed with a 200 m3 air filled storage tank to collect experimental data for validation of literature models and for development of a new CFD model with improved accuracy. The literature models by Fullarton et al. (Fullarton et al. 1987) and Moncalvo et al. (Moncalvo et al. 2016) were chosen for the validation against experimental data. The validation study and experimental results are summarized in this paper, since the full study will be submitted to the International Journal of Loss Prevention in March 2022. In addition, this study compares the experimental data with the results of the new CFD model ARTEM (Advanced Reactor and Storage Tank Emission Model).